Lucidarius in Russia, Belarus, Ukraine, Poland, and Czechia: Types of Reception in the mid-16th to the First Quarter of the 20th Century - Temčinas, Sergejus (Slavistica Vilnensis, 2021)
The article is focused on the problems of historical typology of the Slavic reception of the translated Lucidarius (Lucidář) in Russia, Belarus, Ukraine, Poland, and Czechia throughout its existence. For the first time, a general overview of Slavic evidences is presented in a generalized way, reflecting various types of perception (positive, negative, and neutral) of the specific literary text and indicating the chronology of each of them. Based on these evidences, their historical interpretation is presented, which consists in identifying two qualitatively different stages in the reception of the text under consideration: emotionally engaged (it can equally manifest itself in a positive or negative attitude) and neutral. The change of these historical stages took place in different Slavic countries within half a century (from the 1850s/60s to the 1920s). This process did not depend on the national characteristics of the functioning of Lucidaria, for example, the number of translations performed or their manuscript copies made, as well as the presence or the absence of a local Slavic printed tradition of this particular text, which significantly influenced the degree of its dissemination and, consequently, the level of acquaintance with it in the reading public.
Keywords: Slavic literature; translations; reception; Lucidarius